Pemberdayaan Masyarakat Multisektoral Berbasis Literasi Digital Pada UMKM Pengrajin Genteng di Tulungagung Dalam Pemasaran Produk - Sri Putrianingsih (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2024)
Abstract Along with efforts to increase product sales and income of UMKM in Notorejo Gondang Tulungagung village, digitalization of technology and business is very necessary. This challenge for business people and UMKM is also a good opportunity. Currently, the internet is an effective marketing medium for many consumers. The use of social media is also increasingly widespread as a medium for online promotion and sales. This research examines multisectoral community empowerment based on digital literacy with a focus on UMKM (Micro, Small, and Medium Enterprises) in the roof tile industry. This empowerment aims to increase the capabilities and independence of UMKM through the use of digital technology in the learning and production process. With digital literacy, UMKM players can access information, expand marketing networks, and increase production efficiency.